Motivational background of confl icts among preschool and early school-aged children - Cywińska, Małgorzata (Wydawnictwo Naukowe UAM, 2013)
The motivational background of interpersonal conflicts developing among preschool- and early school-aged children comprises competitive, normative and identity-related aspects. The motives provide a basis for distinguishing different types of childhood confl icts: competitive conflicts, conflicts of norms, and conflicts originating from the sense of identity. Competitive conflicts arise due to the following motives underlying children’s conflict-inducing interactions: the motive of possession, attractiveness, maintaining a bond with a partner or recognition. Confl icts of norms, on the other hand, are refl ected in the motive of loyalty and in the motive of absolute compliance with rules adopted for games and other activities. Confl icts motivated by the sense of identity focus on defending one’s rights or views. Teachers, educators and parents should be familiar with reasons that trigger confl icts among children in middle and late childhood in order to be able to properly organize the teaching and education process, and constructively resolve any emerging confl icts, thus giving confl icts a developmental dimension. Adequate understanding of motivations underlying children’s confl icts also determines the process of developing the culture of confl ict among children.
Motywacyjne tło konfliktów między przedszkolakami i dziećmi w wieku szkolnym
Motywacyjne tło konfliktów interpersonalnych między przedszkolakami i dziećmi w wieku szkolnym obejmuje aspekt konkurencyjny, normatywny i tożsamościowy. Rodzaje motywów stanowią podstawę dla odróżniania różnych rodzajów dziecięcych konfliktów: konflikty na tle konkurencyjnym (motyw posiadania, atrakcyjności lub uznania), konflikty norm (motyw lojalności i absolutnej zgodności z zasadami przyjętymi dla różnych działań) i konflikty związane z poczuciem tożsamości (motyw własnych praw i przekonań). Aby właściwie konstruować proces nauczania i edukacji oraz konstruktywnie rozwiązywać konflikty, nauczyciele, pedagodzy i rodzice powinni być zaznajomieni z przyczynami wywołującymi konflikty między dziećmi.
Keywords: interpersonal conflict; stages of the conflict process; stage of entry into conflict; motives of conflict interactions among children; conflict types; konflikty interpersonalne; fazy konfliktów; motywy konfliktów; typy konfliktów